Impact of Films on Attitudes and Behavior of Adolescents and Efforts in Moral Development: Dampak Film Terhadap Sikap Dan Perilaku Remaja Serta Upaya Dalam Pembinaan Akhlak - Puspadewi, Diny; ETIS, Nyong (Universitas Muhammadiyah Sidoarjo, 2020)
Introduction: Most of today's Indonesian films are filled with love themes aimed at teenagers who are connoisseurs of these film genres. So that indirectly it has an impact on adolescent psychology both negatively and positively. Research objectives: The purpose of this study was to determine the impact of films on adolescent attitudes and behavior as well as actions in improving moral quality. Methods: The research design used was descriptive qualitative with a phenomenological approach. The data collection techniques were in-depth interviews, observation, and documentation. Result: This study resulted in the finding that films do have an impact on adolescent psychology both from the negative and the positive side. The negative impact on films can cause disruption to adolescent development because not all adolescents have the ability to filter what can be imitated or not and the positive impact that can be taken is that films can be used as a medium or source that can help adolescents understand the world and have an effect. for children's emotional intelligence. Preventive actions for improving the quality of students with strategies in the process of student behavior towards devotion to the Creator and strategies in the process of student behavior towards their social environment